2016
DOI: 10.1117/1.jnp.10.012524
|View full text |Cite
|
Sign up to set email alerts
|

Memristive model of hysteretic field emission from carbon nanotube arrays

Abstract: Some instances of electron field emitters are characterized by frequency-dependent hysteresis in their current-voltage characteristics. We argue that such emitters can be classified as memristive systems and introduce a general framework to describe their response. As a specific example of our approach, we consider field emission from a carbon nanotube array. Our experimental results demonstrate a low-field hysteresis, which is likely caused by an electrostatic alignment of some of the nanotubes in the applied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…We found that memristive switching of a carbon nanotube is related to the formation and subsequent redistribution of a non-uniform elastic strain and piezoelectric charge in a nanotube under the influence of an external electric field [ 18 , 19 , 20 , 21 , 22 ]. In addition, the presence of flexoelectric and piezoelectric properties in CNTs could explain the phenomenon of hysteresis of the current-voltage characteristics in the study of the emission properties of vertically aligned carbon nanotubes (VA CNTs) and electric parameters of nanotube bundles, which still has not been unambiguously explained [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that memristive switching of a carbon nanotube is related to the formation and subsequent redistribution of a non-uniform elastic strain and piezoelectric charge in a nanotube under the influence of an external electric field [ 18 , 19 , 20 , 21 , 22 ]. In addition, the presence of flexoelectric and piezoelectric properties in CNTs could explain the phenomenon of hysteresis of the current-voltage characteristics in the study of the emission properties of vertically aligned carbon nanotubes (VA CNTs) and electric parameters of nanotube bundles, which still has not been unambiguously explained [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hysteresis in current–voltage characteristics is useful for memory devices commonly referred to as memristors . Memristive devices are novel elements of electric circuits, in which the relation between output and input signals is determined by a dynamic internal state variable .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Hysteresis in field emission is ubiquitous (e.g., see refs. [4,[11][12][13][14]). It is therefore important to develop a transparent and functional theory that would describe different hysteretic dependences possibly exhibiting nontrivial behavior such as abrupt changes or self-crossings.…”
Section: Introductionmentioning
confidence: 99%
“…Проведенные экспериментальные исследования показали, что индивидуальные ориентированные углеродные нанотрубки проявляют воспроизводимый мемристорный эффект, связанный с их деформацией и возникновением внутреннего электрического поля [11,12]. Также имеются сообщения о наблюдении эффекта переключения сопротивления при исследовании эмиссионных характеристик массивов вертикально ориентированных УНТ [13][14][15][16] и при исследовании пучков УНТ методом сканирующей туннельной микроскопии (СТМ) [17]. При этом переключение сопротивления УНТ происходило из высокоомного в низкоомное состояние, что не согласуется с теорией электромеханического эффекта, проявляющегося в увеличении сопротивления УНТ в процессе ее деформации [18].…”
Section: Introductionunclassified
“…Анализ публикаций [11][12][13][14][15][16][17][18][19] показал, что необходимым условием проявления мемристорного эффекта является предварительное формирование в ориентированной УНТ неравномерной упругой деформации, которая приводит к возникновению пьезоэлектрических зарядов и форми-рованию внутренней напряженности поля в нанотрубке [18,[20][21][22]. Последующее приложение внешнего электрического поля к неравномерно деформированной УНТ вызывает перераспределение деформации в ней и, как следствие, изменение сопротивления.…”
Section: Introductionunclassified